2016
DOI: 10.1093/infdis/jiw545
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s sarcoma-associated herpesvirus infection of neurons in HIV positive patients

Abstract: Our study showed that KSHV infects human CNS-resident cells, primarily neurons, in HIV-positive Zambian individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Adjacent 6 µm-thick sections of paraffin-embedded KS tissues were used for IHC, as previously described [55]. Mouse anti-LANA antibody clone NCL-L-HHV8-LNA (1:100) (Leica Biosystems, Newcastle, UK), antihuman CD8 clone C8/144B (1:100) (Agilent, Santa Clara, CA) or anti-human CD8 clone 4B11 (1:40) (GeneTex, Irvine, CA) were used as primary antibodies.…”
Section: Immunohistochemistry (Ihc) and Cell Quantificationmentioning
confidence: 99%
“…Adjacent 6 µm-thick sections of paraffin-embedded KS tissues were used for IHC, as previously described [55]. Mouse anti-LANA antibody clone NCL-L-HHV8-LNA (1:100) (Leica Biosystems, Newcastle, UK), antihuman CD8 clone C8/144B (1:100) (Agilent, Santa Clara, CA) or anti-human CD8 clone 4B11 (1:40) (GeneTex, Irvine, CA) were used as primary antibodies.…”
Section: Immunohistochemistry (Ihc) and Cell Quantificationmentioning
confidence: 99%
“…Virus infections are the most frequent reason for encephalitis. A variety of viruses affect the CNS and induce encephalitis, including flaviviruses such as Dengue [ 275 , 276 ], hepatitis C [ 277 ], Japanese encephalitis [ 278 , 279 ], West Nile [ 44 ] and Zika [ 280 282 ], as well as herpes viruses such as herpes simplex [ 283 ], varicella Zoster [ 284 ] and Kaposi’s sarcoma associated herpes virus [ 285 ], as well as HIV [ 286 , 287 ]. All the viruses mentioned above may infect microglia [ 276 278 , 280 , 281 , 288 ], whereas flaviviruses and herpes viruses, but not HIV [ 289 ], may also infect neurons and/or astroglia.…”
Section: Introductionmentioning
confidence: 99%
“…KSHV is in the same family as Epstein-Barr virus (EBV), the virus that causes infectious mononucleosis (mono) and is linked to several types of cancer [49]. Recent studies have found a strong link between the activity of specific viral species (three herpesviruses: HSV1 HHV-6 and HHV-7), with molecular, genetic, clinical, and neuropathological aspects of AD [50,51].…”
Section: Discussionmentioning
confidence: 99%